The Strategies of Learning Writing Used by EFL Learners at a Higher Education Institution - Rika Junianti; Bambang Widi Pratolo; Arifiana Tri Wulandari (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
Writing is the process of structuring ideas and sharpening intelligence. The students should understand and think about many things to produce good writing. This research addresses two research objectives: (1) what strategies the students use in learning writing skills, and (2) what problems the students have in learning the writing skill. The subjects of this study are 35 EFL students of English Departments in an Indonesian higher education institution. They were invited to complete a questionnaire of strategies in learning writing skills, and six of them were asked to have an interview about the problems during the learning process. The strategies are based on the stages of the writing process (planning, execution, and revision), which in this research were presented in three model factors (cognitive, metacognitive, and social strategies). The result showed that the average use for each strategy is as follows, 79% for metacognitive strategy, 74% for cognitive strategy, and 81% for social strategy. Regarding the second goal of this study, the problems that the students faced in learning writing include grammar and vocabulary issues.